Numerical Study of Leakage and Rotordynamic Performance of Staggered Labyrinth Seals Working with Supercritical Carbon Dioxide - Hao Cao; Wanfu Zhang; Lu Yin; Li Yang (Shock and Vibration)
The numerical model of a staggered labyrinth seal working with supercritical carbon dioxide (S–CO2) is established. The dynamic and static characteristics of the staggered labyrinth seal for different axial shifting distances of the rotor, various cavity geometries (heights/widths of the rotor convex plate, heights of the seal cavity), and seal clearances were investigated and compared with the conventional see-through labyrinth seal. The results show that the effective damping coefficient (Ceff) with positive axial shifting distance is higher than that with negative axial shifting distance. When the rotor with convex plate operates without axial shifting, the cross-coupled complex dynamic stiffness (hR) of the staggered labyrinth seal shows little effect on the Ceff, and the average direct damping (Cavg) has a dominant influence on the Ceff. As the whirling frequency (Ω) is lower than 60 Hz, the Ceff decreases with increasing height of the rotor convex plate. For Ω < 140 Hz, the damping coefficient generally increases with the decreasing height of the seal cavity. For Ω < 160 Hz, the Ceff of the see-through labyrinth seal is about 107%–649% of the staggered labyrinth seal. Otherwise, the Ceff of the staggered labyrinth seal is about 105%–113% of the see-through labyrinth seal. The Ceff of the seal with the rotor convex plate width of 5.13 mm is relatively high, which is conducive to the stability of the system. The Ceff increases with the decreasing seal clearance. The Ceff of the seal with 0.4 mm clearance is about 116%–148% the seal with 0.6 mm. The leakage flow rate of the staggered labyrinth seal of the see-through labyrinth seal is increased by about 45.5%. The leakage flow rate of the staggered labyrinth seal decreases with the increasing convex plate height, the seal cavity height, and the decreasing seal clearance.